COVID-19, new challenges to human safety: a global review - Aikebaier, Saierdaer (Frontiers in Public Health, 2024)
In the context of sustainable human development, human safety has gradually shifted from traditional state and political conflict to social conflict and horizontal inequality, and the pandemic has exacerbated this variation risk. This study includes literature from 40 countries on five continents since 2020, explored and tidy up the impacts of pandemics on human safety based on three perspectives: personal safety, family safety and social safety, refined the macroscopic concept of human safety. The comprehensibility of the global review conclusions is enhanced by combining it with Maslow's hierarchy of needs. Finally, some novel and comparative results are included to broaden the understanding of the impact of the pandemic, and help policymaker better understand human safety changes from a new perspective.